Price Perception, Promotion, And Environmental Awareness With Mediation Of Trust In Purchase Intentions For Rooftop Solar Power Plants : Adyasolar Case Study - Akhmad Adi Kusnanto; Didik J Rachbini; Dudi Permana (Dinasti Publisher, 2023)
As life develops and the population increases, the need for electricity becomes increasingly important, especially in Indonesia. The challenge of supplying electricity to the people is facing obstacles. The problem is limited fossil fuels (coal and oil). The Rooftop Solar Power Generation System is the process of generating electricity using photovoltaic modules that are installed and placed on the roof, walls or other parts of the Rooftop Solar Power Plant customer's building and supplying electrical energy through the transfer customer's Rooftop Solar Power Generation electricity connection system. The aim of this research is to empirically demonstrate the influence of perceived price, promotion and environmental awareness by instilling confidence in the intention to purchase a Rooftop Solar Power Plant. The results of this study are price perception, advertising and environmental awareness have a positive effect by instilling confidence in the purchase intention of Rooftop Solar Power Plants.